2017
DOI: 10.1155/2017/2198323
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Prevents IL‐1β‐Induced Apoptosis in Human Nucleus Pulposus via the PI3K/AKT Pathway

Abstract: Purpose To explore the effect and possible mechanism of icariin, a prenylated flavonol glycoside derived from the Chinese herb Epimedium sagittatum that was applied to IL-1β pretreated human nucleus pulposus (NP) cells. Methods Human NP cells were isolated from intervertebral discs of patients with scoliosis and lumbar spondylolisthesis. The cells were divided into five groups: A (blank control); B (20 ng/ml IL-1β); C (20 ng/ml IL-1β + 20 μM icariin); D (20 μM icariin + 20 ng/ml IL-1β + 25 μM LY294002); E (20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Many studies have shown that the pathological process of cisplatin-induced renal cell apoptosis is related to the release of many inflammatory mediators such as TNF-α and IL-1β [36,37]. A study by Deng et al has demonstrated that icariin has a significant anti-inflammatory effect [20]. Therefore, we hypothesized that icariin might exert anti-inflammatory effects on cisplatin-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Many studies have shown that the pathological process of cisplatin-induced renal cell apoptosis is related to the release of many inflammatory mediators such as TNF-α and IL-1β [36,37]. A study by Deng et al has demonstrated that icariin has a significant anti-inflammatory effect [20]. Therefore, we hypothesized that icariin might exert anti-inflammatory effects on cisplatin-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 91%
“…3A, cisplatin exposure for 24 h reduced HEK-293 cell viability in a dose-dependent manner. Compared with normal control group, the experimental groups (5,10,20,40, and 80 μM of cisplatin) exerts significantly statistical differences on cell viability (p < 0.05 or p < 0.01 or p < 0.001). According to the results, 20 μM (p < 0.01) was chosen for the subsequent experiments.…”
Section: Icariin Protected Cisplatin-induced Cell Damage On Hek-293 Cmentioning
confidence: 90%
See 1 more Smart Citation
“…PUR could attenuate hippocampal neuronal injury through the PI3K/Akt1/GSK-3β signaling pathway [29]. In our previous studies, the PI3K/Akt signaling pathway was found to be significantly activated in the protective effect of icariin on human NPCs [30] in unfavorable inflammatory microenvironment. Since PUR can protect the neurocyte also through the PI3K/Akt signaling pathway, it assumes that this mechanism may be adapted to the effects of PUR on NPMSCs.…”
Section: Introductionmentioning
confidence: 90%
“…PUR could efficaciously restore compressioninduced decrease of PI3K and p-Akt levels in the cytoplasm, while LY294002 administration abrogated this effect radically (Figures 2(b) and 2(c)). Besides, PUR at 200 μM and LY294002 at 25 μM [30] had no effects on cell death and apoptosis, if PUR and LY294002 were pretreated alone without compression ( Supplementary Figure 4 and Supplementary Figure 8).…”
Section: Pi3k/akt Pathway Was Altered In Npmscs Under the Effects Of mentioning
confidence: 96%